Narrative science : reasoning, representing and knowing since 1800 - Morgan, Mary S. (Cambridge University Press, 2022)
Narrative Science examines the use of narrative in scientific research over the last two centuries. It brings together an international group of scholars who have engaged in intense collaboration to find and develop crucial cases of narrative in science. Motivated and coordinated by the Narrative Science project, funded by the European Research Council, this volume offers integrated and insightful essays examining cases that run the gamut from geology to psychology, chemistry, physics, botany, mathematics, epidemiology, and biological engineering. Taking in shipwrecks, human evolution, military intelligence, and mass extinctions, this landmark study revises our understanding of what science is, and the roles of narrative in scientists' work. This title is also available as Open Access.
Title from publisher's bibliographic system (viewed on 28 Sep 2022).
Keywords: Communication in science.; Research -- Methodology.